On finite dimensional Lie algebras of planar vector fields with rational coefficients - Petravchuk, A. P.; Makedonskyi, Ie. (Methods of Functional Analysis and Topology, 2013)
The Lie algebra of planar vector fields with coefficients from the field of rational functions over an algebraically closed field of characteristic zero is considered. We find all finite-dimensional Lie algebras that can be realized as subalgebras of this algebra.